Finger Enslaving in the Dominant and Non-Dominant Hand - Wilhelm, Luke A. (2013)
During single-finger force production, the non-instructed fingers unintentionally produce force (finger enslaving). In this study, enslaving effects were compared between the dominant and non-dominant hands. The test consisted of a series of maximum voluntary contractions with different finger combinations. Enslaving matrices were calculated by means of training an artificial neural network. The dominant hand was found to be stronger, but there was found to be no difference between the overall enslaving effects in the dominant and non-dominant hands. There was no correlation between the magnitude of finger enslaving and the performance in such tests as the Edinburgh Handedness Inventory, the Grooved Pegboard test, and the Jebsen-Taylor Hand Function test. Each one of those three tests showed a significant difference between the dominant and non-dominant hand performances. Eleven subjects were retested after two months, and it was found that enslaving effects did not fluctuate significantly between the two testing sessions. While the dominant and non-dominant hands are involved differently in everyday tasks, e.g. in writing or eating, this practice does not cause significant differences in enslaving between the hands.